Animation Narrative on Stress Relief and Psychological Cognitive Development in Adolescents. (2nd September 2022) - Jiang, Qian; Ma, Li; Yue, Min
Abstract : As the atmosphere of domestic animation is getting stronger and stronger in recent years, its proportion in the process of public aesthetics, entertainment, and consumption is increasing; thus, the relationship between the audience and works has become an important academic focus. The theatrical animation in the animation industry has become the category that needs to be focused on and changed in the development process of domestic animation because of its characteristics of receiving attention from all-age audiences. Because of the diversified audience levels faced by theatrical animation, it is particularly difficult to coordinate the needs of each audience level, coupled with the long-term influence of Japanese and American animation; the trend of pop culture led by network culture; the inheritance, excavation, and reconstruction of national culture; and other cultural environment and creative thinking intertwined, making the construction of the independence of domestic animation appear more and more difficult. The purpose of this paper is to analyze the theoretical study of the healing elements of Natsume Yojimbo and to analyze the creation of Chinese traditional ink and wash in the creation of our own works. It is concluded that the thematic choices are based on two categories: emotions and dreams, which focus on personal life experience and universal concern for human life. The character construction is divided into three aspects: self-resistance and self-reflection, self-vision and self-actualization, and traumatic experience and self-rescue to explain the complexity and diversity of the characters' growth connotation. The narrative perspective constitutes the perspective from which the issues are viewed. The omniscient perspective allows for the coexistence of complex character relationships and a clear storyline, while the limited perspective reveals certain emotional tendencies. The narrative mode presents the moral of the text with cause-and-effect narrative, embellished group narrative, and dreamlike polyphony narrative. Finally, the article discusses the realistic dilemma of the growth narrative of domestic online animation and tries to put forward feasible development suggestions in response to the problems at this stage.